Content, network, and density analysis of the global and Kazakhstani literature on scientometrics - Narbaev, T.; Amirbekova, D.; Sabi, D.; De Marco, A. (BUKETOV BUSINESS REVIEW, 2021)
Object: The current study offers a review of the scientometric literature from Kazakhstan. Methods: Using two literature review approaches (content analysis and scientometric analysis), we conducted content, network, and density analysises. For the content analysis we read the full text of some influential papers in the field. For the network and density analyses, we used the VOSViewer tool. Results: The obtained results showed that there were 17,804 articles in the scientometric literature on the global scale and 22 articles by authors affiliated with Kazakhstan. We used the VOSViewer tool to visualize the trends in the literature. This work’s novelty consists of conducting a critical review of the literature on scientometrics in the Scopus database, the use of analysis methods that did not have been used in scientometric research in Kazakhstan. Secondly, we determined the development level of the scientometric literature in Kazakhstan. Conclusions: The major findings can be used to assist researchers and policy makers in science management in determining the evolutionary scientometric characteristics of the global literature, in general, and the Kazakhstani literature, in particular, as well as to identify patterns in the development of science